A dynamic high-gain design for prescribed-time regulation of nonlinear systems. (May 2020) - Krishnamurthy, Prashanth; Khorrami, Farshad; Krstic, Miroslav
Abstract: "Prescribed-time" stabilization addresses the problem of regulating the state to the origin in a fixed (prescribed) time irrespective of the initial state. While prior results on prescribed-time stabilization considered specific classes of systems such as a chain of integrators with uncertainties matched with the control input (i.e., normal form), we address here a general class of nonlinear systems in a generalized strict-feedback-like structure with state-dependent nonlinear uncertainties throughout the system dynamics. The proposed control design is based on our dynamic high gain scaling technique along with a novel temporal transformation and form of the scaling dynamics with temporal forcing terms. We show that the proposed control design achieves prescribed-time stabilization for the considered general class of uncertain nonlinear systems.